Laboratory Simulation Study for Modelling Bare Soil Evaporation from Different Soil Layers in Root Zone - Ingle, V. K.; Mishra, A. K.; Singh, D. K.; Ramasubramanian, V. (Journal of Agricultural Engineering, 2013)
Bare soil evaporation (Es) is a predominant component of water balance during early growth stages of irrigated field crops, row crops with incomplete cover and in soils having shallow water table. Besides being a loss of precious water, it influences many other hydrologic and ecological processes. Laboratory simulation studies were conducted to characterize Es in two soil types, namely silty clay loam (SCL) and sandy loam (SL). Root zone water balance approach was used to estimate the Es. Results indicated that Es from top 0-15 cm soil depth in SCL soil varied from 2.0 to 3.0 mm.d-1 in the initial stage, which subsequently rose to 3.9 mm.d-1 in the drying stage. For SL soil, it varied from a minimum of 2.0 to a maximum of 3.8 mm.d-1 in 0-15 cm soil layer. Multiple linear regression models were developed to assess Es using the predominant meteorological parameters affecting the evaporation process. Validation with the field observations showed very close agreement with predicted results. The results of this study could be used in NCR region for the assessment of Es for similar soil types.